(untitled) - Boyd, Claude E (Auburn University, Ala., 1992)
Water and soil analyses commonly needed in aquacultural research or in making decisions on water quality management in aquaculture ponds are described in this manual. Most procedures are useful in both freshwater and brackish water. In addition to providing a "step-by-step" account of each procedure, in most instances, some explanation of the basis of each is provided
Quản lý chất lượng nước trong nuôi trồng thủy sản,Quản lý chất lượng nước hệ thống nuôi thủy sản
Keywords: Aquaculture,Water quality,Pond soils,Thủy sản,Đất đáy ao,Chất lượng nước; Water-supply,Testing,Testing,Analysis,Cung cấp nước,Thí nghiệm,Phân tích,Thí nghiệm